The potential of zeolites in palm oil industry - Sharifah Bee Derouane-Abd Hamid (Malaysian Palm Oil Board (MPOB), 2015)
Natural modernite, an analog of large pore zeolite has been shown to be effective to bleach the colour of crude palm oil (CPO) and refined bleached deodorized palm oil (RBDPO) at a low dosage of less than 1 wt.% at oil temperature of approximately 100 degrees celcius. The colour improve significantly from 23R+40Y to 20R+10Y upon its addition. The current and conventional bleaching agent used in physical refinery, i.e. bleaching earth, give comparable performance. Taking into consideration of zeolite properties as an absorbent and ion-exchange, it is suspected that the bleaching treatment can also produce positive effect with regard to improving the odour of the oil, besides removing undesirable impurities and oil- and non-oil components that may be present. The Bronsted acidity in zeolite has also been used in the esterification of oleic acid with oleic alcohol, using ultrastable ZY zeolites as catalysts. USY zeolites do not catalyze the formation of esters with 38 or more carbon atoms, but are more active and selective for those with 32-34 and 36 carbon atoms.